Domesticated Landscapes in Araucaria Forests, Southern Brazil: A Multispecies Local Conservation-by-Use System - Reis, Maurício S.; Montagna, Tiago; Mattos, Andréa G.; Filippon, Samantha; Ladio, Ana H.; Marques, Anésio da Cunha; Zechini, Alex A.; Peroni, Nivaldo; Mantovani, Adelar (Frontiers in Ecology and Evolution, 2018)
Araucaria forest is a sub-tropical component of the Atlantic Forest Biome, occurring between 18º S and 30º S latitude, and 500 to 1800 m altitude in Southern and Southwestern Brazil and Northwestern Argentina. In recent history (20th century), this forest has undergone non-sustainable exploitation and reduction in area dedicated to agricultural and forestry use. However, smallholders continue using several resources from this forest, even adapting management systems. The main system is geared towards the production of yerba mate (Ilex paraguariensis) under Araucaria trees (Araucaria angustifolia), which holds economic, cultural and social relevance for thousands of farmers. Seeking evidence of domestication and conservation of the resources managed in this system, we compared different landscapes on the Northern Plateau of Santa Catarina in Southern Brazil. Focusing on three species – yerba mate, Araucaria and caraguatá (Bromelia antiacantha) – we characterized management practices (interviews and guided tours), demographic structure (permanent plots in farming zones and in a protected area) and genetic diversity in populations from farming zones and from a protected area. Demographic structure and genetic diversity from different landscapes were compared to evaluate the system potential for conservation. The results indicated that the three species are intentionally promoted with practices of protection, transplanting and/or selection, in different ways and with different functions (caraguatá hedges, yerba mate harvesting and collection of pinhões – seed-like nuts of araucaria). Landscapes are managed for yerba mate harvesting and cattle raising, for both economic and cultural reasons, with a consequent reduction in the density of most other plant species. In all cases the genetic diversity of the species was high for most of the sampled properties, and the set of farmers’ populations did not differ from the protected area. The set of populations of each species operates as a metapopulation and local management practices contribute to conservation. Thus, management systems and practices conducted by farmers maintain the landscape with productive forest fragments, favoring the conservation-by-use of these species. The system requires these management practices, which bring about changes in various species and are motivated by cultural and economic factors, in order to maintain the domestication of these